Local Consumer Behaviour in Developing Countries toward Food and Drinks with Honey Labels: Evidence from Indonesia - Abdillah, Fatimah; Maryam, Suryani; Sakti, B. Retno Pratiwi; Juhari, Ahmad (Politeknik Negeri Bandung, 2025)
This analysis aimed to provide evidence of local consumer behaviour toward food and drinks with honey label utilizing the Theory of Planned Behaviour. Specifically, the effect of health consciousness, perceived nutritional content, and perceived behaviour control on attitude and purchase intention were analyzed. The quantitative design with a survey method was used, and the samples were 271 respondents, while the data underwent analysis through the application of structural equation modelling utilizing AMOS 24 software. Perceived nutritional content positively and significantly affects purchase intention through attitude. Perceived behaviour control showed a direct positive impact on attitude and purchase intention. The findings also showed that attitude played an important role in mediation, stimulating consumer intention to purchase food and drinks with honey label. This research theoretically contributed to the understanding of the correlation of perceived nutritional content and behaviour control in the context of healthy-label food and drinks, based on the TPB. The focus was specifically on honey label, informing perceived health benefits. This research can serve as a foundation for marketers to establish the most efficient marketing communication approach for food and beverage goods with a honey label. Consumer perceptions are dynamic and may necessitate more targeted research based on the product category.